Vitamin D endocrine system: VDR binding, nutrition and drugs development - Norman, Anthony (Henry Stewart Talks, 2007)
VDR conformational ensemble, A vitamin D receptor ensemble model, X-ray crystal structure of the nuclear vitamin D receptor, VDR G- and A-pocket, Vitamin D nutrition for good health, Sources of vitamin D, How much vitamin D do we need?, World-wide vitamin D nutrition status, Vitamin D status and intestinal calcium absorption, New research frontiers, Drug development, Alopecia, Analogs of hormone D are effective for psoriasis, hormone-D activates the innate immune system -Vitamin D in human disease states
Archived at 2021/02/25